PCR-Based Identification of Oral Streptococcal Species - Jeffrey A. Banas; Min Zhu; Deborah V. Dawson; Huojun Cao; Steven M. Levy (International Journal of Dentistry)
The microbial etiology of dental caries is still debated. Among the hypothesized contributors are the “low pH streptococci,” a designation given to unusually acid proficient strains among the primary plaque colonizers S. oralis, S. mitis, S. gordonii, and S. anginosus. However, accurate assignment of species is difficult among the oral streptococci. Our objective was to develop a streamlined method for identifying strains of S. oralis and S. mitis from plaque samples so that they could be analyzed in a separate study devoted to low pH streptococci and caries. Two independent PCR amplifications of a locus highly conserved among streptococci were used for presumptive species identification. Multilocus sequence analysis (MLSA) was used to measure accuracy. Sensitivity was 100% for selecting S. oralis and S. mitis among the clones sampled. Specificity was good except for the most closely related species that could not be reliably distinguished even by MLSA. The results with S. oralis and S. mitis were used to identify new primer sets that expanded the utility of the approach to other oral streptococcal species. These novel primer sets offer a convenient means of presumptive identification that will have utility in many studies where large scale, in-depth genomic analyses are not practical.